Tinjauan Yuridis terhadap Pelaksanaan Pengendalian Pemanfaatan Ruang Wilayah Kabupaten/Kota (Studi Kasus di Kota Yogyakarta) - Muhammad Hasyim (Jurnal Hukum IUS QUIA IUSTUM, 2003)
The implementation of the area usage control in Yogyakarta City territory is still ineffective. This caused by the lack of institution. Which spectically perform integrated and comprehensive area control function inform of supervision and arrangement and in implementing supervision toward Local Regulation No 5 1988 implementation about Built Permit for Buildings (Ijin Membangun Bangunan/IMBB) and usage Permit of Buildings. City Order Office only focused on the availability ofIMBB by party who intended to build certain building and the appophateness of the building according criteria provided by IMBB.